Hopes, tensions and complexity: Indian students' reflections on the relationship of values to management education and future career options - Siememsma, Fran (1998)
This case study was undertaken to explore the way postgraduate management students relate their personal values to their current education and future career aspirations. The research primarily focused on the perceptions of students enrolled in an elective course offered by the Management Centre for Human Values. Indian Institute of Management, Calcutta (IIMC). Students' attitudes towards Western postgraduate management programme were elicited through interviews and group discussions. Their diverse attitudes are analysed under the themes of gender; personal identity; age and status; ethics, religion and spirituality; profit and wealth; as well as consumerism and environmentalism. The opinions of the students are quoted directly to illustrate their experience of tension and ambiguity, as they anticipated moving from an academic to a business role. - Reproduced
Keywords: Management education